Role of PPARα in Hepatic Carbohydrate Metabolism. (9th August 2010) - Peeters, Annelies; Baes, Myriam
Abstract : Tight control of storage and synthesis of glucose during nutritional transitions is essential to maintain blood glucose levels, a process in which the liver has a central role. PPARα is the master regulator of lipid metabolism during fasting, but evidence is emerging for a role of PPARα in balancing glucose homeostasis as well. By using PPARα ligands and PPARα − / − mice, several crucial genes were shown to be regulated by PPARα in a direct or indirect way. We here review recent evidence that PPARα contributes to the adaptation of hepatic carbohydrate metabolism during the fed-to-fasted or fasted-to-fed transition in rodents.